The answer is 20 because you dive it
Answer:
x = 5/8 plz give branliest
Step-by-step explanation:
Using the equation,![1 = \frac{1}{8} + x + \frac{2}{8}](https://tex.z-dn.net/?f=1%20%3D%20%5Cfrac%7B1%7D%7B8%7D%20%20%2B%20x%20%2B%20%5Cfrac%7B2%7D%7B8%7D)
simplify 1 = x + ![\frac{3}{8}](https://tex.z-dn.net/?f=%5Cfrac%7B3%7D%7B8%7D)
1 -
= x
= x
Answer:
108?
Step-by-step explanation:
Answer:Hope This Helps ☺️
Step-by-step explanation:
She is not correct because she did not substitute the same number in both expressions in Step 1
Step-by-step explanation:
CASE 1: substitute 1 for x to both sides of the equations
L.H.S
-(4x-5)+2(x-3)
-(4 (1) - 5)+ 2(1-3) = - (-1) + 2(-2) = 1 - 4 = -3
R.H.S
-2x - 5
-2(1) - 5 = -2-5 = -7
Hence for x= 1
-(4x-5)+2(x-3) ≠ -2x -5
Because -3 ≠ -7
CASE 2: substitute -1 for x to both sides of the equations
L.H.S
-(4x-5)+2(x-3)
-(4 (-1) - 5)+ 2(-1-3) = - (-9) + 2(-4) = 9 - 8 = 1
R.H.S
-2x - 5
-2(-1) - 5 = 2-5 = -3
Hence for x= -1
-(4x-5)+2(x-3) ≠ -2x -5
Because 1 ≠ -3
Answer:
She is not correct because she did not substitute the same number in both expressions in Step 1
Answer:
nope cant even think not meh
Step-by-step explanation:
sorry